A review on fast food consumption behaviour in Sindora Berhad / Nurul Ain Mohd Salleh - Mohd Salleh, Nurul Ain (Faculty of Business and Management, 2011)
This study explores the roles of societal development factors towards fast food consumption among employees in Sindora Berhad. The main purpose is to identify whether the societal development factors influence fast food consumption in Sindora Berhad. The study also had been conduct to inform the employees the level of fast food consumption taken in the organization. The societal development factors were identified and measure through questions covering time constraints, new demographic, away-from-home eating habits and new consumer tastes and preferences in identifying fast food consumption level.